The Hong Kong connection - Cooper, Peter (Edinburg Gate : Longman, 1996)
"Longman Originals" is a series of graded readers in four stages. All the stories are original - that is to say, written especially for the series. Originated from the "Longman Structural Readers", the series aims to offer a stimulating range of modern stories, including detective stories, adventure and romance. In this stage 4 reader, a dead body is found by the side of a railway line in London. Chief Superintendent Robert Scott leads the investigation and is soon on the trail of a gang of ruthless jewel thieves, a trail that leads to Hong Kong.
Stage 4.
Keywords: English language -- Textbooks for foreign speakers; English language -- Study and teaching; English language -- Study and teaching -- Textbooks for foreign speakers